IMPLEMENTATION OF BREAST SELF-EXAMINATION IN BREAST CANCER PREVENTION IN ADOLESCENTS: A LITERATURE REVIEW - Meinita Wulansari; Lisa Ardiningtyas; Rasmar Yanti; Ramlah Milawati Ramli (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
In particular for teenagers, Breast cancer is one of the leading causes of sickness and death worldwide, and breast self-examination is an essential tool for its early diagnosis, and knowledge of the importance of this examination is essential to prevent this disease. Performing breast self-examination regularly helps adolescents to recognize changes in their breasts. In addition, breast self-examination also serves as an initial step to detect abnormalities, which if found early, can increase the chances of recovery. Although many adolescents already understand the importance of breast self-examination, additional socialization and motivation are still needed to encourage them to carry out regular examinations. Educational activities that involve direct interaction and discussion can increase adolescents' understanding and awareness of breast cancer and how crucial early identification is. The application of self-examination for breast cancer in preventing breast cancer in adolescents is very important and must be supported by effective education and ongoing motivation.